Shade Matching of OMNICHROMA Analyzed by Four Digital and Visual Shade Selection Techniques: An In Vitro Study - Abdalwahab M Al-Hadithi; Mohammed K Gholam (Wolters Kluwer Medknow Publications, 2022)
Introduction: To evaluate the shade matching of teeth restored with OMNICHROMA using four different teeth shade-selection techniques. Methods: Thirty sound upper first premolar teeth were used. Shade was taken by the VITA Linearguide 3D-MASTER, the VITA Easyshade V, digital photography, and the TRIOS 3 intraoral scanner for the cervical area. Subsequently, a Class V cavity was prepared and filled with an OMNICHROMA filling, and another reading for the shade was taken. Results: Value of ΔE in all groups were significantly higher than the clinically acceptable value (ΔE: 3.7) (P < 0.001). One-way ANOVA measurements showed statistically significant differences among the groups (P < 0.001). Conclusion: OMNICHROMA composite showed some degree of mismatch with the surrounding tooth structure. This in vitro model could not simulate complex oral situation and more clinical studies are necessary.